Dysphemisms and language change in ZANU-PF and MDC political discourse - Dziya, Dr Hlamba (IJRDO- Journal of Educational Research, 2017)
The aim of this paper is to explore dysphemisms that are used by the Zimbabwe African National Union Patriotic Front, (ZANU-PF) and the Movement For Democratic Change (MDC) politicians in six Zimbabwean newspapers before and after the signing of the SADC mediated Global Political Agreement (GPA) that ended the political deadlock between the parties in 2008. In this study, I argue that after the signing of the GPA, political discourse between the parties does not only change considerably, but it also becomes progressively and markedly more dysphemistic and more combative in nature than was the case before the GPA was signed. I hold the view that linguistic analysis of this genre of political discourse might shed light on the psychology of those who use it.